Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

Mondialisation et harmonisation : vers l’émergence d’un cadre normatif à caractère régional des affaires Africain. Cas Maroc-OHADA - Rabhi, Tauofik (Annales de l’Université d’Alger, 2021)
Partant du constat que le droit est un phénomène social, l’harmonisation des législations apparaît indispensable au développement de zones économiques d’échange comme le sont la Communauté européenne et l'Accord de libre-échange nord-américain. Harmoniser, c’est dégager des directions et des orientations communes, établir des principes et des règles de base communs. En effet, dans un contexte de mondialisation et de globalisation il s’est opérées de grandes mutations économiques contemporaines modifiant ainsi les conditions du développement de certains pays africains, incitant désormais un mouvement d’intégration juridique en fonction des facteurs économiques, politiques, sociaux voire stratégique. Sur le plan économique, il y un rapprochement juridique visant l’harmonisation des législations et une intégration juridique qui s’est manifestée par une ouverture vers l’extérieur adoptant une politique de libéralisme économique. Le Maroc, de part son positionnement géographique a exprimé son désir de faire partie de ce rapprochement juridique on exprimant sa volonté à adhérer à l’OHADA.

Le mimétisme juridique dans le droit de l'OHADA - Leyo, Desmond Vidor (Université Toulouse 1 Capitole, 2021)
Au sens général, le mimétisme s’entend de toute reproduction des gestes, des attitudes d’autrui. En droit, le mimétisme est considéré comme la transposition de certaines règles juridiques d’un Etat vers un autre. Ainsi, l’objectif général de la réalisation de notre recherche vise à étudier en quoi le droit de l’OHADA est dominé par une telle pratique dans l’édiction des Actes uniformes alors que la règle de droit doit être élaborée en fonction des besoins du peuple qu’elle est destinée à régir. La mondialisation de l'économie exige l'harmonisation des droits et des pratiques du droit. Cette exigence constitue pour des pays en développement comme les nôtres une priorité pour créer les conditions favorables à l'instauration d'un espace de sécurité juridique et judiciaire indispensable pour drainer des flux importants d'investissements, car investir est déjà en soi un risque, même s'il est calculé; s'il faut doubler ce risque premier inéluctable de celui d'un système juridique fluctuant, ondoyant et insaisissable, il n'y aura pas beaucoup de possibilités d’attirer des investisseurs. C’est dans cette optique que les Etats de l’Afrique francophone, notamment, ont pensé à juste titre élaborer une législation uniforme et moderne en vue de pallier les insuffisances et la vétusté des multiples législations nationales. En effet, le principal point faible du dispositif mis en place par l’OHADA réside dans son éloignement des réalités socio-économiques et culturelles africaines. Or, il est écrit dans l’esprit des lois que « les lois doivent être tellement propres au peuple pour lequel elles ont été faites, que c’est un très grand hasard si celles d’une nation peuvent convenir à une autre… ».Dans le même sens, le professeur Michelle Alliot affirmait que « le droit d’un pays est lié aux habitudes d’un peuple, à sa mentalité, à ses croyances religieuse, qu’il devrait être impossible d’appliquer aux peuples africains le droit de la France ».Ainsi, à l’examen de l’état de la législation de l’organisation pour l’harmonisation en Afrique du droit des affaires, la plupart des textes étudiés, notamment ses Actes uniformes, montrent que le droit de l’OHADA n’a pas répondu au souci de territorialité, autrement dit, aux réalités sociales des Etats membres. Il permet de constater que le législateur communautaire a transposé de façon « plagiaire » les prescriptions étrangères, notamment françaises, à l’occasion de ses interventions. Ce mimétisme juridique peut être expliqué, entre autres causes très diverses, par le « fait colonial » qui, quoique révolue politiquement, continue d’influencer beaucoup de pays africains dont les lois ne sont pas toujours en harmonie avec leurs réalités socio-économiques. Dans le cadre de l’OHADA, l’étude du mimétisme juridique pose la question relative à d’énormes difficultés que génère ce phénomène compliquant d’autant l’application du droit uniforme dans les pays membres. Malgré de nombreux handicaps ou difficultés qu’il engendre, le mimétisme juridique dans le droit de l’OHADA a une portée qui peut s’avérer très considérable car il est considéré comme une méthode de construction de ce droit. L’objectif de notre thèse est non seulement de montrer ou démontrer l’existence du mimétisme juridique dans l’espace OHADA, les faiblesses ou handicaps qu’il y présente ou qu’il y génère, les atouts qu’il peut y marquer, mais également son devenir ou son avenir en termes de vivacité.
Keywords: CCJA; Cour Commune de Justice et d'Arbitrage; Institutions politiques; Législateur; Pays de l'OHADA

Le système juridique unitaire à l’épreuve du droit coutumier : la nécessité d’une territorialisation du droit - Guémar, Carine (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The unitary legal system vs. customary law: the need of territorialization. The French State is a unitary State as opposed to federal States, in which there is one Constitution providing for provisions applicable throughout the territory of the French Republic. Unity can be found in a legal unity first, in this the unitary Law is the one that does not admit of territorial differenciation. A political and organic unity, since there is only one Parliament, one Government. A social unity eventually, which consists of the admission of a single French people. If the French tradition is based on a centralized system, the implementation of the process of territorial decentralization led to reconsider the uniformity of the Law precisely with the question of territorial differenciation and territorialisation of Law. The present study proposes to return to the consideration by unitary Law of local territories including the overseas territories with the problem of reconciling such a system with customary Law.
Keywords: Customary Law; Overseas territories; Territorial decentralization; Territorialisation of Law; Unitary Law

L'Intégration juridique et le développement économique : contribution à l'analyse économique du droit OHADA - Diawara, Mamadou (Université Cheikh Anta Diop, 2021)
Keywords: Droit OHADA (analyse économique); Développement économique; Intégration juridique

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

Afri̇ka Ülkeleri̇ Hukuku Düzenlemeleri̇nde İrade Muhtari̇yeti̇ - Dürgen, Betül (Africania, 2021)
Çağdaş hukuk düzenlerinde geniş yankı uyandıran irade muhtariyeti ilkesi, kimi zaman maddi hukuk hükümlerinde sözleşme özgürlüğü olarak kendini belli ederken kimi zaman da milletlerarası özel hukuk alanında taraflara hukuk seçimi imkânı ile gündeme gelmektedir. Bazı ülkelerin sınırlandırdığı ölçüde serbest ekonomik düzenlerine dahi etki eden irade muhtariyeti ilkesi, hukukların yeknesaklaştırıldığı kadarıyla uygulanabilir hale gelmektedir. Çalışmamıza konu olan Afrika kıtası ülkelerinde, hukukun yeknesaklaştırılması gereği bölgede anlaşılmış olup gerekli adımların atıldığı OHADA kanunları ile açığa çıkarılmıştır. Bunun dışında yer yer milletlerarası özel hukukta genel olarak kabul görmüş bağlama noktaları dışına çıkan ülke bazında uygulamaların söz konusu olduğu da görülmektedir. Çalışmamızın amacı irade muhtariyeti prensibinin milletlerarası özel hukuka yansıması olan hukuk seçiminin Afrika’da uygulanabilir olup olmadığını tespit etmektir. Bu tespiti yapmak Afrika ülkelerindeki çeşitli uygulamaların çağdaş düzenlemeler ile karşılaştırılmasını gerektirmiştir
Keywords: OHADA; Party autonomy; applicable law; choosing law; hukuk seçimi; irade muhtariyeti; milletlerarası özel hukuk; private international law; uygulanacak hukuk

L'influence de l'Union européenne sur les processus d'intégration en Afrique de l'Ouest - Sow, Abdoulaye (Université Jean Moulin Lyon 3, 2021)
L'Union européenne exerce une influence active et une influence passive sur les organisations régionales africaines. L'influence active résulte de l’action extérieure de l'UE. L’Union s'emploie, par le biais ses relations conventionnelles, à exporter son modèle et à assurer la promotion de ses valeurs. L'influence passive est, quant à elle, plutôt une influence subie. C'est une influence voulue et désirée par les organisations régionales africaines. Cette influence n’est pas imposée ou exercée, elle découle de la force d'attraction du modèle européen. En effet, l’Union européenne, en dehors de toute politique conventionnelle, est objet de fascination. Ce sont ces deux formes d'influence qu'aborde cette étude. L'objectif central de la recherche est d'interroger les similitudes, mais aussi de questionner la pertinence de la transposition du modèle européen dans un environnement autre que le sien. Les logiques d'intégration n’étant pas identiques, les organisations régionales africaines optent pour un mimétisme juridique et institutionnel limité. The European Union exerts both active and passive influence on African regional organizations. The active influence results from the EU's external action. The EU is working towards, through its conventional relations, to export its model and promote its values. Passive influence, on the other hand, is rather a suffered influence. This is an influence wanted and desired by African regional organizations. This influence is not inflicted, imposed or exerted; it derives from the attraction of the European model. Indeed, the European Union, besides any conventional policy, is object of fascination. It is these two forms of influence that this study addresses. The central objective of the research is to question the similarities, but also to question the relevance of the implementation of the European model in an environment other than its own. Since the logics of integration are not identical, African regional organizations opt for limited legal and institutional mimicry.
Keywords: Active influence; African community law; Attraction; Communauté économique des États de l'Afrique de l'Ouest; Contribution économique et politique; Cooperation; Coopération; Droit; Droit communautaire africain; Droit communautaire européen; Droit de la CEDEAO; Droit de l’UE; Droit de l’UEMOA; Droit européen; ECOWAS law; EU law; Economic and political contribution; European community law; Force de séduction; Grafting and rejection; Greffe et rejet; Imitation; Import; Importation; Influence; Influence active; Influence passive; Institutional and legal mimicry; Mimétisme institutionnel et juridique; Passive influence; Relations extérieures; Reprise; Régionalisme (politique internationale); Seductive strength; Transposition; Union européenne; Upturn; WAEMU law

Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması - Babayev, Ilgar (İstanbul Ticaret Üniversitesi, 2021)
Uluslararası ticaretin gelişimi ve artması dünyadaki bütün devletler tarafından hedeflenen bir amaçtır. Ancak devletlerin ulusal hukuk sistemleri arasındaki farklar bu gelişim için belirli engeller oluşturmaktadır. Bu engelleri aşmak için uluslararası ticaret hukukunun yeknesaklaştırılması, yani aynı uluslararası hukuki işleme uygulanacak iki veya daha çok ulusal hukuk sisteminin farklı kurallarının bir kuralla değiştirilmesi çare olarak görülmektedir. Bu amaçla şimdiye kadar bir çok çalışmalar yapılmış ve bir çok yeknesaklaştırma aracı ortaya konulmuştur. Uluslararası ticaret hukukunun bel kemiğini oluşturan uluslararası ticari sözleşmeler alanında hazırlanmış olan yeknesaklaştırma araçları ise bu bakımdan özellikle önem taşımaktadır. Hukukun yeknesaklaştırılması alanında çalışmalar sürdürülmekle birlikte bu konuya şüpheyle bakanlar ve yeknesaklaştırmanın kendi amacına ulaşamayacağını düşünenler de mevcuttur. Bu yeknesaklaştırma sürecinde ortaya çıkan bir takım sorunlarla ilgilidir. Ancak özellikle de uluslararası ticaret hukuku alanında yapılan yeknesaklaştırma çalışmalarında elde edilen başarılar umut vaat etmektedir. Uluslararası ticari sözleşmeler hukuku alanında yapılmış olan ayrı ayrı yeknesaklaştırma çalışmaları ile ilgili araştırmalar mevcut olsa da, konuyu daha kapsamlı bir şekilde ele alan ve meseleye daha geniş bir perspektiften bakan araştırmaların eksik olduğunu görmekteyiz. Özellikle de Türkiye'de bu tür araştırmalarda bir boşluğun mevcut olduğu hissedilmektedir. Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması amacıyla ortaya konulmuş çalışmaların ve hazırlanmış olan araçların daha kapsamlı bir şekilde araştırılması, onların sağladığı faydaları göstermek, bu alanda ortaya çıkan sorunları belirlemek ve gerekli çözüm önerileri sunmak açısından önem arz etmektedir. Bütün bunları dikkate alarak biz bu araştırmamızda uluslararası ticaret hukukunun yeknesaklaştırılması kavramını, onun önemini ve sağladığı avantajları, yeknesaklaştırmanın gerçekleştirilmesi yöntemlerini, uluslararası ticaret hukukunun yeknesaklaştırılması alanında çalışmalar yapan ve bu sürece katkıda bulunan uluslararası kurumları, uluslararası ticari sözleşmeler alanında yapılmış olan ve şu an yapılmakta olan çalışmaları, bu konuyla ilgili ortaya çıkan sorunları ve bu sorunların ortadan kaldırılması için sunulan çözüm önerilerini incelemeye çalıştık. [...] The development and growth of international trade is an aim targeted by all states in the world. However, the differences between the national legal systems of states pose certain obstacles to this development. To overcome these obstacles, the unification of the international commercial law is considered a remedy, that is, changing the different rules of two or more national legal systems to be applied to the same international legal process with one rule. For this purpose, so far many studies have been done and many unification instruments have been introduced. The unification instruments prepared in the field of the international commercial contracts, which form the backbone of international commercial law, are particularly important in this regard. Although studies on the unification of the law continues, there are also those who are skeptical about this issue and those who think that it cannot achieve its own goal. It concerns a number of problems that arise in the process of unification. However, the successes achieved in the unification studies especially in the field of international commercial law promise hope. Although there are researches on individual unification studies in the field of international commercial contracts law, we see that there is a lack of research that covers the issue more extensively and looks at the issue from a wider perspecitve. Especially, a vacancy in this kind of research is available in Turkey. It is important to investigate the studies and the instruments that have been prepared for the purpose of the unification of the international commercial contracts law, to show their benefits, to identify the problems that arise in this field and to offer necessary solutions. Considering all these, in this research, we tried to examine the concept of the unification of the international commercial law, its importance and advantages, the methods of realization of unification, the international institutions that work in the field of the unification of the international commercial law and contribute to this process, the problems that arise about this issue and the proposed solutions to eliminate these problems.
Keywords: Hukukun Yeknesaklaştırılması; International Commercial Contracts Law; International Commercial Law; International commercial contracts; Lex Mercatoria; Uluslararası Ticaret Hukuku; Uluslararası Ticari Sözleşmeler; Uluslararası Ticari Sözleşmeler Hukuku; Unification Instruments; Unification of Law; Yeknesaklaştırma Araçları

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.